Gastrointestinal Mucormycosis: A Rare but Lethal Mimicker of Necrotising Enterocolitis - Radhakrishna, Veerbhadra; Govindarajan, Krishna Kumar; Balachandar, Bharathi; Plakkal, Nishad; Jinkala, Sree Rekha (Journal of Nepal Paediatric Society, 2016)
Neonatal Gastrointestinal mucormycosis is a rare fungal infection carrying high morbidity and mortality. Clinically, it is not easily distinguishable from the more common necrotizing enterocolitis. Diagnosis is made by histopathology of the involved bowel. We report a neonate with gastrointestinal mucormycosis, bringing to notice the fatality of this infection. J Nepal Paediatr Soc 2016;36(2):198-200.